A decentralized and service‐based solution for data mediation: the case for data providing service compositions. (23rd May 2013) - Sellami, Mohamed; Gaaloul, Walid; Defude, Bruno
Summary: The last few years have seen an increase in the use of e‐services as a natural consequence of the service‐based economy growth. However, the distributed nature of services can raise several heterogeneity problems that can hamper the widespread adoption of service‐oriented architectures (SOA). In this paper, we are interested in data heterogeneity problems that can occur when using composite services. We propose a service‐based approach for automatically inserting appropriate mediation services in service compositions to resolve structural heterogeneities in their data flow. This mediation is ensured through a special kind of Web services called data mapping Web services. In addition, in order to be in agreement with the distributed nature of the Web, we propose a decentralized solution to publish/discover these services. We demonstrate how our approach applies to the data structural heterogeneity problem in data providing service compositions as a particular data heterogeneity case. Provided experimental results show that our approach is efficient in realistic situations. Copyright © 2013 John Wiley & Sons, Ltd.